Episode-of-Care Characteristics and Costs for Hip and Knee Replacement Surgery in Hospitals Belonging to the High Value Healthcare Collaborative Compared With Similar Hospitals in the Same Health Care Markets. Issue 6 (June 2017) - Weeks, William B.; Schoellkopf, William J.; Ballard, David J.; Kaplan, Gary S.; James, Brent; Weinstein, James N.
Abstract : Background: To inform consumers and restrain health care cost growth, efforts to promote transparency and to reimburse for care episodes are accelerating in the United States. Objective: To compare characteristics and costs of 30-day episode of care for hip and knee replacement occurring in High Value Healthcare Collaborative (HVHC)-member hospitals to those occurring in like non–HVHC-member hospitals in the same 15 health care markets before interventions by HVHC members to improve health care value for those interventions. Research Design: This is a retrospective analysis of fee-for-service Medicare data from 2012 and 2013. Subjects: For hip arthroplasty, 4030 HVHC-member and 7572 non–HVHC-member, and for knee arthroplasty, 6542 HVHC-member and 13, 900 non–HVHC-member fee-for-service Medicare patients aged 65 and older. Measures: Volumes, patient demographics, hospital stay characteristics, and acute and postacute care standardized costs for a 30-day episode of care. Results: HVHC-member hospitals differed from similar non–HVHC-member hospitals in the same health care markets when considering volumes of surgeries, patient demographics, Charlson scores, and patient distance to care during the index admission. There was little variation in acute care costs of hip or knee replacement surgery across health care markets; however, there was substantial variation in postacute care costs across those same markets. We saw less variation in postacute care costs within markets than across markets. Regression analyses showed that HVHC-member status was not associated with shorter lengths of stay, different complication rates, or lower total or postacute care costs for hip or knee replacement. Conclusions: Health care regions appear to be a more important predictor of episode costs of care than HVHC status. Abstract : Supplemental Digital Content is available in the text.